Geriatric Oncology Workshop (GrOW): Development and Evaluation of a Nationwide Nursing Curriculum. Issue 4 (May 2021) - Burhenn, Peggy; Economou, Denice; Uranga, Carolina; Okamoto, Christopher; Kim, Heeyoung; Roberts, Elsa; Sun, Can-Lan; Arsenyan, Anait; Yang, Richard; Chang, Howard; Mitani, Dale; Katheria, Vani; et al.
Abstract: Introduction: Oncology nurses are key in caring for older adults with cancer, but few have received specialized training in gerontology. To address this, a geriatric oncology curriculum was developed for oncology nurses. Materials & Methods: The Geriatric Oncology Workshop (GrOW) was developed and delivered to oncology nurses ( n  = 387) from 2016 to 2019. Workshops were evaluated using: 1) Assessment of preparedness, comfort, and skills; 2) Knowledge gained; 3) Participant evaluations of workshop (4-point Likert-type scale); 4) Faculty evaluations (10-point Likert-type scale); and 5) Follow-up assessment of goals. Descriptive statistics (frequencies, proportions, medians, means) were used to describe participants and results. Paired t -test was used to evaluate participants' knowledge gain, and linear mixed modeling was used to evaluate longitudinal changes in preparedness, comfort, and skill levels. Results: Overall, 387 oncology nurses participated in GrOW. Participant-rated workshop evaluation means were 3.7 to 3.9. Overall, nurses had statistically significant increases in pre- to post- questionnaire scores of 18.8% ( p  < 0.001) in workshop 1, 26.8% ( p  < 0.001) in workshop 2, 24.9% ( p  < 0.001) in workshop 3, and 18.6% ( p  < 0.001) in workshop 4, with an overall mean of 22.4% ( p  < 0.001) knowledge gained for all four workshops. Nurses reported an increase in skill, comfort, and preparedness at 18 months for workshop 1, 2, and 3 and in skill and comfort at 12 months for workshop 4 ( p  < 0.01). Faculty evaluation scores ranged from 9.3 to 10.0. Discussion: A geriatric oncology curriculum designed for oncology nurses can improve levels of evidence-based knowledge and provide more skill, comfort, and preparedness in caring for this population.